Investigation of Non-cardiac Findings in Conotruncal Heart Diseases in Children - Gülce Gökmen; Halise Zeynep Genç; İbrahim Cansaran Tanıdır; Erkut Öztürk (Cam & Sakura Medical Journal, 2023)
Objective: Individuals with conotruncal heart disease (CHD) often exhibit a range of associated anomalies. Our study aimed to investigate the frequency of non-cardiac comorbidities in patients with CHD. Material and Methods: Our study was a hospital-based, single-center, retrospective, observational study conducted at our clinic between August 1, 2020, and November 1, 2022. The study included 179 cases, both male and female, aged between 0 day and 6 months, with CHDs diagnosed. Data from each patient, including gender, complete blood count, biochemical and coagulation tests, abdominal ultrasound (USG), cranial USG, and serum immune globulin levels, were evaluated. Results: In 14.5% of the 179 patients included in the study, abnormal renal function test results were detected. In 18.4% of the cases, abnormal liver function test results were detected. When evaluated according to the diagnosis group, among the 21 patients diagnosed with interrupted aortic arch (IAA), 7 (33.3%) had abnormal liver function test results. In 25.7% of the cases, the leukocyte count was abnormal. In 12.8% of the cases, the platelet count in the complete blood count was abnormal. In 10.6% of the cases, abnormal results were found in the coagulation tests. In 21.2% of the cases, abnormal results were found in the serum immunoglobulin (Ig) and Ig subgroups. When evaluated according to the diagnosis group, among the 21 patients diagnosed with IAA, 10 (47.6%) had abnormal results. In 19% of the cases, abdominal USG results were pathological, and in 9.5% of the cases, cranial USG results were pathological. Conclusion: CHD in children may be accompanied by non-cardiac problems that cause hemodynamic and systemic problems and affect organ systems. Routine liver function tests, renal function tests, coagulation, complete blood count, immune screening, and abdominal USG evaluation may be useful to improve the quality of life of patients and reduce morbidity and mortality while waiting for necessary surgical interventions.